ANALYSIS OF PERFORMANCE-BASED SEISMIC DESIGN METHODS ON 60-STOREY TALL BUILDING WITH COMBINATION OF FLAT SLAB AND SHEAR WALL STRUCTURAL SYSTEMS - Arya Perdana, Gilang
Flat slab is an innovation in the world of civil engineering. In this study, an analysis of performance-based seismic design methods on a 60-storey building with a total height of 240 meters with a combination of a flat slab and shear wall structural system with additional outriggers and belt-truss. In SNI 1726:2012 there is a height limit of 48 meters for seismic design category D so to ignore this height limit, the flat slab element is only given a gravity load in other words it cannot withstand earthquake loads and the shear wall element is given a gravity load and lateral load. Based on the linear analysis, it was found that the shear wall received a base shear force of 95.6% so that it can be said that the entire base shear force was received by the shear wall. This proves the flat slab as a gravity system and the core wall as a seismic resistant system. Based on pushover and non-linear time history analysis, it was found that the performance of the structure is still in IO-LS condition so that it can ignore the height limit of SNI 1726:2012 and shows that the coupling beam element is the biggest energy dissipator of a structure that uses a flat slab so that coupling beam reinforcement is very important. . According to SNI 2847:2013, coupling beams with an L/H of 2.67, which means they are between 2-4, may be given diagonal reinforcement or without diagonal reinforcement. Where the coupling beam must be checked for failure against bending. Based on pushover analysis, the performance of coupling beam reinforcement with diagonal reinforcement is 40%LS and without diagonal reinforcement is 60%LS. These results are in accordance with the results of David Naish's research, where the coupling beam with diagonal reinforcement provides a greater hysteresis loop than without diagonal. Based on non-linear time history analysis, it was found that coupling beam reinforcement with diagonal reinforcement gave 40%LS performance where the results were the same as pushover analysis.